2022
DOI: 10.3389/fnut.2022.786421
|View full text |Cite
|
Sign up to set email alerts
|

Color Shade Nets Affect Plant Growth and Seasonal Leaf Quality of Camellia sinensis Grown in Mississippi, the United States

Abstract: Shading modifies the microenvironment and can provide plants with some protection from frequent heat, drought, frost, and hail induced by climate change and has the potential to improve plant growth, yield, and quality. Tea (Camellia sinensis) is an ancient plant originating from tropical and subtropical regions and prefers to grow in partial shade under the forest canopy. The emerging tea industry in the United States (US) requires research support on establishing tea fields in novel environmental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…Shading is one of the best ways to protect plants from different temperatures such as cold, hot, highs and low temperatures, and hence decrease cold damage or leaf injury in plants [35]. In present research, cold damage was detected under non-shading conditions during both mild and extreme conditions.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Shading is one of the best ways to protect plants from different temperatures such as cold, hot, highs and low temperatures, and hence decrease cold damage or leaf injury in plants [35]. In present research, cold damage was detected under non-shading conditions during both mild and extreme conditions.…”
Section: Discussionmentioning
confidence: 47%
“…In the development of tea plants, different shade treatments had a substantial impact on chlorophyll and biochemical components, as well as carbon and nitrogen regulation [24,35,43]. Photosynthesis and photosynthetic pigments can deliver energy for specialized metabolism of plants and carbon and nitrogen are both crucial for synthesis of photosynthetic products, enzymes, and chloroplasts in plants [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, short-term strategies are needed to alleviate important environmental stresses and increase plant growth and development. Shade is one of the finest strategies to protect plants from various temperature stressors ( Zaman et al., 2022 ) to increase growth and productivity and reduce cold damage or leaf injury in plants ( Zhang et al., 2022 ). The present study showed cold damage to C. sinensis leaves in three shading groups compared with no-shade control plants in November and December during low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of shade nets is a typical practice across various climatic settings to protect different crops on physiological, molecular, and cellular levels ( Ji et al., 2018 ). Several researchers published studies on different tea cultivars in response to protective shading mechanisms under different environmental conditions ( Ji et al., 2018 ; Zhang et al., 2022 ). Zaman et al.…”
Section: Introductionmentioning
confidence: 99%
“…The lower the P/A ratio, the higher the catechin quality index, which will ultimately enhance the overall quality of green tea [ 31 , 47 , 48 ]. Numerous studies have demonstrated that shading can increase the foliar content of theanine, because shade-grown plants assimilate more nitrogen and theanine breaks down less [ 39 , 48 , 49 , 50 ]. In summer afternoons, the high temperature and strong light in tea plantations may lead to the photoinhibition of tea [ 51 ].…”
Section: Discussionmentioning
confidence: 99%